Multipath Routing Optimization with Interference Consideration in Wireless Ad hoc Network - He, Junxiao; Yang, Oliver; Zhou, Yifeng; Issa, Omneya (Ad Hoc Networks, 2016)
This paper proposes a multipath routing optimization algorithm for allocating bandwidth resources to nodes that are subject to interference from flows in other parts of the network. The algorithm consists of three steps: path discovery, path selection and load distribution. In addition to delay, power and hop count, the routing metric also takes into account the interference of flows from other parts of the network during path selection and load distribution. An optimization model is formulated based on the flow cost and the bandwidth usage by the other flows. The AIMMS package is used to solve the optimization problem to obtain an optimal solution with the minimum total flow cost. Finally, we use computer simulations to assess the performance and effectiveness of the proposed routing technique.